On Characterization of Inextensible Flows of Tangent Developable Surfaces of Time like Biharmonic General Helices in the Lorentzian E(1, 1) - Korpinar, Talat; Turhan, Essin (Chiang Mai Univ, Fac Science, 2013)
In this paper, we study inextensible flows of tangent developable surfaces of timelike biharmonic general helices in the Lorentzian group of rigid motions E(1, 1). We obtain the corresponding equations for the inextensible flow of tangent developable surfaces of timelike biharmonic general helices in the Lorentzian group of rigid motions E(1, 1).
Keywords: biharmonic curve; bienergy; general helix; geometric flows; harmonic map